Laterality effects of human pudendal nerve stimulation on corticoanal pathways: evidence for functional asymmetry. (1st July 1999) - Hamdy, S; Enck, P; Aziz, Q; Uengoergil, S; Hobson, A; Thompson, D G
Abstract : BACKGROUND: Although motor and sensory pathways to the human external anal sphincter are bilateral, a unilateral pudendal neuropathy may still disrupt anal continence. Anal continence can, however, be preserved despite unilateral pudendal damage, and so to explain those differing observations, we postulated that pudendal innervation might be asymmetric. AIMS: To explore the individual effects of right and left pudendal nerve stimulation on the corticofugal pathways to the human external anal sphincter and thus assess evidence for functional asymmetric pelvic innervation. METHODS: In eight healthy subjects, anal sphincter electromyographic responses, evoked to transcranial magnetic stimulation of the motor cortex, were recorded 5–500 msec after digital transrectal electrical conditioning stimuli applied to each pudendal nerve. RESULTS: Right or left pudendal nerve stimulation evoked anal responses of similar latencies but asymmetric amplitudes in six subjects: dominant responses (>50% contralateral side) from the right pudendal in four subjects and from the left in two. Cortical stimulation also evoked anal responses with amplitude 448 (121) μV and latency 20.9 (1.1) msec. When cortical stimulation was preceded by pudendal nerve stimulation, the cortical responses were facilitated at interstimulus intervals of 5–20 msec. Dominant pudendal nerve stimulation induced greater facilitation of the cortically evoked responses than the non-dominant nerve. CONCLUSIONS: Cortical pathways to the external anal sphincter are facilitated by pudendal nerve conditioning, in an asymmetric manner. This functional asymmetry may explain the presence and absence of anal incontinence after unilateral pudendal nerve injury.